On Sums of Overlapping Products of Independent Bernoulli Random Variables - Csörgö, S.; Wu, W. B. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We find the exact distribution of an arbitrary remainder of an infinite sum of overlapping products of a sequence of independent Bernoulli random variables.